1998
DOI: 10.1093/oxfordjournals.jbchem.a022078
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Chloramphenicol/H+ Antiport in Cmr (MdfA) System of Escherichia coli and Properties of the Antiporter

Abstract: We detected chloramphenicol/H+ antiport activity in membrane vesicles of Escherichia coli and cloned a gene for the antiporter from chromosomal DNA of E. coli. Introduction of the gene into E. coli cells conferred resistance to chloramphenicol and ethidium. A slight increase in resistance to acridine orange was also observed. Elevated chloramphenicol efflux and ethidium efflux were observed in cells harboring a plasmid carrying the gene. Addition of chloramphenicol to the assay mixture reduced the efflux of et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 3 publications
2
62
0
Order By: Relevance
“…Although the DmexXY mutant (PA7 DXY) showed the same antimicrobial susceptibility pattern as the DmexXY-oprA mutant (PA7 DXYA), the DoprA mutant (PA7 DA) did not show any significant difference to the wild-type strain PA7, suggesting that another outer-membrane protein(s) complements the oprA deletion. In P. aeruginosa PAO1, the MexXY system utilizes OprM of the multidrug efflux operon mexAB-oprM as its outer membrane component (Mine et al, 1999;Aires et al, 1999). In fact, the DoprA DoprM double mutant (PA7 DA DM) showed the same susceptibility to the aminoglycosides, although the DoprM mutant (PA7 DM) did not; therefore, MexXY utilizes OprM in addition to OprA as one of its outer membrane components in PA7.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the DmexXY mutant (PA7 DXY) showed the same antimicrobial susceptibility pattern as the DmexXY-oprA mutant (PA7 DXYA), the DoprA mutant (PA7 DA) did not show any significant difference to the wild-type strain PA7, suggesting that another outer-membrane protein(s) complements the oprA deletion. In P. aeruginosa PAO1, the MexXY system utilizes OprM of the multidrug efflux operon mexAB-oprM as its outer membrane component (Mine et al, 1999;Aires et al, 1999). In fact, the DoprA DoprM double mutant (PA7 DA DM) showed the same susceptibility to the aminoglycosides, although the DoprM mutant (PA7 DM) did not; therefore, MexXY utilizes OprM in addition to OprA as one of its outer membrane components in PA7.…”
Section: Resultsmentioning
confidence: 99%
“…This strain is very useful for the analysis of various multidrug efflux pumps from micro-organisms (Morita et al, 1998;Mine et al, 1999;Masaoka et al, 2000) and plants (Li et al, 2002). E. coli KAM3 containing the mexXY or mexXY-oprA genes of PA7 showed increased resistance to a number of antibiotics, including erythromycin, ciprofloxacin, cefpirome, tetracycline and gentamicin (Table 2) to the same extent as E. coli KAM3 containing the mexXY genes of P. aeruginosa PAO1 (data not shown).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…In several clinically isolated mutants of P. aeruginosa, higher expression of RND-type efflux pumps was observed (Hirai et al, 1987;Rella & Haas, 1982;Wolter et al, 2004). Of the 11 RND efflux pumps identified in this organism, 10 pumps, MexAB-OprM (Poole et al, 1993), MexCD-OprJ (Poole et al, 1996), MexEF-OprN (Kohler et al, 1997), MexGHI-OpmD (Aendekerk et al, 2002;Sekiya et al, 2003), MexJK (Chuanchuen et al, 2002), MexMN (Mima et al, 2005), MexPQ-OpmE (Mima et al, 2005), MexVW (Li et al, 2003), MexXY (Mine et al, 1999;Westbrock-Wadman et al, 1999) and TriABCOpmH (Mima et al, 2007), have been experimentally confirmed, and their properties have been reported. The RND-type efflux pump usually consists of three components to fulfil the function properly and includes an innermembrane component (RND component), a periplasmic component (MFP component), and an outer-membrane component (OMP component) (Touze et al, 2004), and the three-dimensional structures of MexA, MexB and OprM have been reported (Akama et al, 2004a, b;Higgins et al, 2004;Sennhauser et al, 2009).…”
Section: Introductionmentioning
confidence: 94%